Mechanical properties of GGBS-based polyethylene engineered cementitious composite (PE-ECC) at elevated temperature - Fardin Mahmoudi; Jamal A. Abdalla; Rami A. Hawileh (Results in Engineering)
Engineered Cementitious Composite (ECC) is known for its multiple cracking and significant strain-hardening behaviors. While polyethylene-based ECC (PE-ECC) has demonstrated superior structural performance at ambient temperature, its behavior under elevated temperature remains relatively underexplored. Additionally, ECC is characterized by high cement content. This study investigates the impact of both elevated temperatures and cement substitution with Ground Granulated Blast Furnace Slag (GGBS) at levels of 40 % and 60 % (denoted as G40 and G60, respectively) on the mechanical and micromechanical properties of GGBS-based High Strength and High Ductility (HSHD) PE-ECCs. Compression tests were conducted after heating up to 800 °C, while tensile and flexural tests were performed on specimens heated to 120 °C and 200 °C, respectively. The results indicated that the increase in GGBS from 40 % to 60 % correlated with a decrease in compressive strength. Specimens with 40 % GGBS replacement showed compressive strengths of 31.1 MPa and 23.2 MPa after temperature exposures of 600 °C and 800 °C, retaining 43.6 % and 32.5 % of the control samples’ strength, respectively. Additionally, empirical equations were derived to estimate the residual compressive strengths of PE-ECC specimens. All tensile samples heated up to 120 °C exhibited strain-hardening and multiple cracking behaviors, while those exposed to 200 °C failed brittlely after the first crack. In general, G40 showed higher tensile strength than G60, while G60 showed higher tensile strain at all temperatures. Prisms exhibited multiple cracking and deflection-hardening up to 120 °C. G40 specimens demonstrated higher flexural strengths across all temperature levels and exhibited greater deflection values than G60 at both room temperature and 120 °C.